OC-011 Endoscopic therapy in barrett's oesophagus (be) with HGD (high grade dysplasia) and early malignancy; a prospective, single centre experience. (28th May 2012) - McEwan, H C; Morris, A J; Glen, P; Abela, J E; Going, J J; Fullarton, G
Abstract : Introduction: There is increasing evidence that endoscopic therapy in BE with a combination of endoscopic mucosal resection (EMR) and radiofrequency ablation (RFA) is an effective treatment of intramucosal cancer (IMC) and HGD. The widespread application of this therapy is yet to be assessed in the UK outside the trial setting. We present here the results of a single centre study from a large tertiary referral teaching hospital. We aim to assess the efficacy and safety of endoscopic therapy with EMR and RFA in the treatment of HGD and IMC. Methods: 102 consenting patients with a mean age of 69 (range 42–89) with HGD or IMC were enrolled between July 2008 and September 2011. All pathology was reviewed by a pathologist with a particular interest in Barrett's. The treatment protocol involved EMR of all nodular areas with subsequent RFA of all remaining Barretts epithelium. The RFA technique involved a combination of circumferential RFA (HALO 360) followed by subsequent focal ablation (HALO 90) of residual areas of Barrett's tongues or islands. The UK protocol involved a maximum of two HALO 360's and 3 HALO 90's. Results: 102 patients have been recruited (30 with IMC and 72 with HGD). Fifty patients have completed the treatment protocol (median of 1 HALO 360 and 1 HALO 90) and of these, 52% had initial EMR. Median follow-up in this group was 9 months (range 3–41). Thirteen of these 50 patients had IMC (26%) with 37 patients demonstrating flat HGD only. Of the 102 patients recruited, nine patients (8.7%) have progressed to invasive malignancy after a median of 12 months. As a result, there were 59 patients who exited the protocol following an intention to treat. To date eradication of dysplasia was achieved in 49/59 patients (83%) and eradication of metaplasia in 40/59 patients (68%). Three patients died from unrelated causes, two from cardiorespiratory comorbidities and one from concurrent lymphoma. Eight patients (8%) developed mild strictures. One patient required readmission for retrosternal pain requiring analgesia. There were no serious complications or peri-procedural mortality. Conclusion: This study demonstrates the efficacy of endotherapy with EMR and RFA in the treatment of IMC and HGD. Although further follow-up is required, these results suggest that such therapy should be offered to all patients as an alternative to surgery. Competing interests: None declared.